Serum S-adenosylmethionine, but not methionine, increases in response to overfeeding in humans - Elshorbagy, A K (Nutr Diabetes, 2016)
BACKGROUND: Plasma concentration of the methyl donor S-adenosylmethionine (SAM) is linearly associated with body mass index (BMI) and fat mass. As SAM is a high-energy compound and a sensor of cellular nutrient status, we hypothesized that SAM would increase with overfeeding. METHODS: Forty normal to overweight men and women were overfed by 1250 kcal per day for 28 days. RESULTS: Serum SAM increased from 106 to 130 nmol/l (P=0.006). In stratified analysis, only those with weight gain above the median (high-weight gainers; average weight gain 3.9±0.3 kg) had increased SAM (+42%, P=0.001), whereas low-weight gainers (weight gain 1.5±0.2 kg) did not (P(interaction)=0.018). Overfeeding did not alter serum concentrations of the SAM precursor, methionine or the products, S-adenosyl-homocysteine and homocysteine. The SAM/SAH (S-adenosylhomocysteine) ratio was unchanged in the total population, but increased in high-weight gainers (+52%, P=0.006, P(interaction) =0.005). Change in SAM correlated positively with change in weight (r=0.33, P=0.041) and fat mass (r=0.44, P=0.009), but not with change in protein intake or plasma methionine, glucose, insulin or low-density lipoprotein (LDL)-cholesterol. CONCLUSION: Overfeeding raised serum SAM in proportion to the fat mass gained. The increase in SAM may help stabilize methionine levels, and denotes a responsiveness of SAM to nutrient state in humans. The role of SAM in human energy metabolism deserves further attention.